2022
DOI: 10.1186/s13054-022-04102-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing PO2 during peripheral veno-arterial ECMO: a narrative review

Abstract: During refractory cardiogenic shock and cardiac arrest, veno-arterial extracorporeal membrane oxygenation (VA-ECMO) is used to restore a circulatory output. However, it also impacts significantly arterial oxygenation. Recent guidelines of the Extracorporeal Life Support Organization (ELSO) recommend targeting postoxygenator partial pressure of oxygen (PPOSTO2) around 150 mmHg. In this narrative review, we intend to summarize the rationale and evidence for this PPOSTO2 target recommendation. Because this is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…For each patient, the probability to show hyperoxia has been estimated using logistic regression. For ATE (average treatment effect on the entire population) analysis, weights have been attributed to each patient of the hyperoxia (overall mean PaO2 > 150 mmHg) and no hyperoxia (overall mean PaO 2 ≤ 150 mmHg) groups, making the two groups similar for the variables in the propensity score [21]. These weights were calculated using the stabilized inverse probability of treatment weighting (SIPTW).…”
Section: Discussionmentioning
confidence: 99%
“…For each patient, the probability to show hyperoxia has been estimated using logistic regression. For ATE (average treatment effect on the entire population) analysis, weights have been attributed to each patient of the hyperoxia (overall mean PaO2 > 150 mmHg) and no hyperoxia (overall mean PaO 2 ≤ 150 mmHg) groups, making the two groups similar for the variables in the propensity score [21]. These weights were calculated using the stabilized inverse probability of treatment weighting (SIPTW).…”
Section: Discussionmentioning
confidence: 99%
“…Whether PaO 2 is obtained from a sample taken in a femoral artery or in each of the radial arteries may result in a wide difference. 3 As a result, patients can be misclassified as hypoxia, normoxia, or hyperoxia just because of the difference in sampling sites. This situation is eased when the native heart and the VA-ECMO flow mixing zone is located after the brachiocephalic trunk and is critical in Harlequin syndrome.…”
Section: Letter To the Editormentioning
confidence: 99%
“…The ELSO guidelines suggest targeting post membrane-normocapnia, but without providing a cut-off value [ 15 ]. A review of the published studies found out that these recommendations were proposed without clear published data [ 16 ]. In the absence of published data, a further question would be if the P post O 2 cutoff value of 150 mmHg proposed by ELSO guidelines can prevent hyperoxemia or hypoxemia.…”
Section: Introductionmentioning
confidence: 99%